The Efficacy and Safety of Tyrosine Kinase Inhibitors for Von Hippel–Lindau Disease: A Retrospective Study of 32 Patients - Ma, Kaifang; Hong, Baoan; Zhou, Jingcheng; Gong, Yanqing; Wang, Jiangyi; Liu, Shengjie; Peng, Xiang; Zhou, Bowen; Zhang, Jiufeng; Xie, Haibiao; Zhang, Kenan; Li, Lei; et al. (Frontiers in Oncology, 2019)
Background: Von Hippel-Lindau (VHL) disease is an autosomal-dominant hereditary cancer syndrome. Currently, studies on tyrosine kinase inhibitor (TKI) therapy for VHL disease are scarce. In this study, we retrospectively evaluated the efficacy and safety of four TKIs in patients with VHL disease. Methods: Patients diagnosed with VHL disease who were receiving TKIs were recruited. Patients were treated with sunitinib (n=12), sorafenib (n=11), axitinib (n=6) or pazopanib (n=3). The therapeutic response was evaluated according to the Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1. Results: From July 2009 to Sept 2018, 32 patients with VHL disease were eligible and included in this study. The median duration of TKI therapy was 22 months (IQR 8.5-44.75), and the median follow-up period was 31.5 months (IQR 13.5-63.5). According to the RECIST, 9 (28%) of 32 patients showed a partial response, 15 (47%) achieved stable disease, and 8 exhibited continued disease progression. A partial response was observed in 11 (31%) of 36 renal cell carcinomas, 4 (27%) of 15 pancreatic lesions and one (20%) of 5 central nervous system (CNS) hemangioblastomas. The average tumor size decreased significantly for renal cell carcinomas (P=0.0001), renal cysts (P=0.027) and pancreatic lesions (P=0.003) after TKI therapy. Common side effects included hand-foot skin reactions, diarrhea, alopecia, thrombocytopenia and fatigue. Conclusions: Partial alleviation of VHL disease-related tumors can be achieved by TKI therapies in some patients, providing an alternative treatment strategy, and the side effects of TKIs are acceptable. Larger prospective studies are warranted to further evaluate the efficacy and safety of TKIs in patients with VHL disease.